An Inclusive AI-Based Game for LIBRAS Learning Developed Through University Extension - da Silva, Italo Firmino; Sebastião, João José; Soares, Ruan Pablo da Silva; Tartare, Beatriz Schuelter; Santos, Gabriel Feltes dos; Vianna, Maria Eduarda Winkel de Mello; Oliveira, Sheila Filipe Pereira; Caneda, Talita Alves Borges; Panisson, Alison R. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
This paper presents IRIS, a university extension project developed within a Computer Engineering program that explores the use of artificial intelligence in the development of educational and inclusive digital games. As part of the project, students design and implement games that apply AI techniques to socially relevant contexts. This paper focuses on one of the project outcomes: an inclusive game inspired by the traditional Hangman game aimed at supporting the learning of Brazilian Sign Language (LIBRAS). The game employs computer vision and artificial intelligence to recognize LIBRAS signs captured by a camera, enabling sign-based interaction instead of text input. The paper describes the main technical aspects of this game and the associated extension activities, highlighting the potential of AI-driven game development in Computer Engineering education and inclusive learning initiatives.